Diversification and internationalization in the European single market: the British exception - Mayer, M; Hautz, J; Stadler, C; Whittington, R (Cambridge University Press, 2017)
This article examines the long-run impact of the 1992 completion of the European Single Market on the diversification and internationalization of European business. It does so at a particular moment of crisis: the exit of the United Kingdom from European Union (“Brexit”). The article finds that completion of the European Single Market is indeed associated with significant and widespread changes in the strategies of European businesses between 1993 and 2010. European business has converged on more focused diversification strategies and followed similar patterns of internationalization. The most significant exception is the consistently low level of British business’s commitment to European markets. The distinctiveness of British internationalization is, in a sense, Brexit foretold.